Pendampingan Penyedia Peningkatan Kapasitas Teknik Desa pada Program Inovasi Desa untuk Meningkatakan Kompetensi Sumber Daya Manusia Di Desa Segunung - Kasnowo (Fakultas Ekonomi Universitas Islam Majapahit, 2022)
Finding problems with service activity partners started with sharing session activities. Partners talk about the need for Human Resources. The partner said that the managers had problems, namely it was difficult to find administrators in the Village Innovation Program, so a competency with minimal resources was needed. The existence of a Village Technical Capacity Building Provider (P2KTD) from the district government is very helpful for the village innovation program, so that activities in Segunung Village can develop. The purpose of this activity is in an effort to improve the management competence of Human Resource Management at Village Technical Capacity Building Providers in Segunung Village, Dlanggu District, Mojokerto Regency. The implementation of activities is carried out by socializing, discussing, and surveying the location that will be used as a place for village development. The results obtained in the form of increasing knowledge and competence of partner HR management for the better.